Evaluation of microwave pyrolysis of oil palm empty fruit bunches - Omar, Rozita (2010)
Agriculture waste such as oil palm empty fruit bunch (EFB) is an environmental concern to our country as one of the world’s biggest oil palm producers. Pyrolysis has been used as a thermal process to treat biomass wastes due to its flexibility in producing solid, liquid and gas products. This study evaluated the possibility to treat EFB via microwave pyrolysis. In this study, the EFB taken from a local oil palm mill was directly placed inside a fixed-bed quartz reactor which was placed in a modified household microwave oven, where both drying and pyrolysis took place simultaneously. Microwave absorbers were added to elevate the reaction temperature so as to reach the required temperature for a pyrolysis reaction to take place. Parameters, such as effects of residence time, addition of inorganic materials (catalysts) and pre-treatment of the EFB, were studied. Meanwhile, a comparison experiment with a conventionally heated reactor was also conducted. Fuel, chemical and dielectric characterization of the EFB undertaken in this study confirmed that it is a good candidate for a microwave pyrolysis process as it is comparable to other biomass. However, dielectric properties of the EFB indicated that it is almost a transparent material to microwave, and for this reason, addition of microwave absorber is required. Studying several microwave absorbers, namely SiC, activated carbons (coconut and palm kernel shell) and char which were produced from a previously conducted experiment, concluded that 5% coconut activated carbon in a granular form was enough to maintain a reaction temperature above 500oC within 15 minutes (60.8oC/min) with highest productivity of 5.1 mol% syngas per g EFB per g absorber. Two types of common pre-treatment, namely cutting and drying, were also studied. Reduction of the EFB size without drying seemed to favor gas production; however, untreated sample was found to give the highest H2 composition but with a similar CH4 concentration as in the other treatments. A slow release of volatile matters in the untreated sample might have provided the opportunity for secondary reaction to produce more H2. Nevertheless, the addition of inorganic materials for tar minimization and syngas enhancement (NaCO3, HSZM5, CaO and CaCO3) did not influence the product distribution. On the other hand, the composition of gas was found to be greatly influenced by the addition of HSZM5, especially H2. Meanwhile, increasing residence time (0.02 - 0.10 s) of volatiles within the reactor was shown to have increased gas composition (increment of 68.4% for H2), particularly for the production of CH4 which resulted in a higher calorific value of the gas. Liquid product (bio-oil) and solid product (char) were also characterized for their potential end use. The char produced in this study has high carbon content (68%), giving it a moderate calorific value at 21.5 MJ/kg, which is similar to that of the commercially produced EFB char, rendering it a good candidate for solid fuel substitute. The EFB char is characterized as mesoporous with highest pore size distribution around 4 nm. The BET surface area is modest at 14.2 m2g-1 and has high mesopore area of 28.3 m2g-1. These characteristics present microwave pyrolysis of EFB as a superior alternative for the carbonization step for activated carbon preparation. Also, EFB char produced from this study is suitable for soil amendment. Highly oxygenated, acidic and viscous bio-oil produced from pyrolysis of EFB has high heating value (30.8 MJ/kg) which is higher than wood tar. Palmitic acid is the most abundant chemical component (12.0-36.4%) in bio-oil. A shorter time was needed in the microwave pyrolysis of EFB compared to the conventional one, and this gives a higher gas production with four times better calorific value (7.6 MJ/m3) but lower calorific value as compared to pyrolyzed coffee hulls and rice straw. The energy cost to produce twelve times higher energy products in the EFB microwave pyrolysis is lower, i.e. at 1.90 cent/MJ as compared to 49.90 cent/MJ in conventional heating. These findings reflect the potential of microwave pyrolysis as an alternative method to both treat waste and produce energy. In summary, EFB was successfully pyrolyzed using microwave as heating source. The bio-oil product has better quality compared to wood oil therefore it has potentially for fuel oil substitute. The char also has the potential for activated carbon or solid fuel. EFB pyrolysis using microwave produced better syngas and cost cheaper compared to conventional heating. Further study is needed to optimize the parameters as to produce product of choice.